The impact of evidence based methodology on the design of doctoral research: a case study - Elisabetta De Marco; Stefania De Santis (Firenze University Press, 2020)
The spreading of the "pedagogical culture of evidence" has triggered a broad debate on the specific contribution of the evidence based methodology to scientific research in the field of educational studies (Calvani, 2007; Calvani & Menichetti, 2013; Hattie, 2016; Ranieri, 2007; Vivanet, 2013). This article presents an application of the evidence based methodology to a doctoral research about the pedagogy of intangible cultural heritage. We have chosen to place the research within a framework of "methodological pluralism" in order to assess the applicability of the Evidence Based Education (EBE) methodology in the initial phase of the research and get to a definition of the key constructs. The implementation of the EBE methodology represents an opportunity for epistemic-methodological rethinking, and an attempt to enrich the vocabulary of pedagogical research with the aim of transferring research methodologies and practices from other disciplines to the pedagogical field.   L'impatto della metodologia evidence based sulla progettazione di una ricerca di dottorato: un caso di studio La diffusione della "cultura pedagogica delle evidenze" è accompagnata da un ampio dibattito sull'apporto specifico della metodologia evidence based alla ricerca scientifica in campo educativo (Calvani, 2007; Calvani & Menichetti, 2013; Hattie, 2016;                                                                                                                                  Ranieri, 2007; Vivanet, 2013). L' articolo presenta un'applicazione della metodologia basata sulle evidenze ad una ricerca di dottorato sulla pedagogia del patrimonio culturale immateriale. L'opzione è di collocare la ricerca in oggetto dentro una cornice di "pluralismo metodologico" per verificare l'applicabilità della metodologia EBE in fase di avvio della ricerca al fine di pervenire ad una definizione dei costrutti chiave. L'applicazione della metodologia EBE si configura come occasione di ripensamento epistemico-metodologico, come tentativo di arricchimento del lessico della ricerca pedagogica al fine di annettere costrutti e pratiche di ricerca di altri settori disciplinari nell'ambito pedagogico.